INTERNALISASI KONSEP MASLAHAH MELALUI BUKU SAKU DALAM MENGUATKAN KARAKTER ISLAMI SISWA DI MTs NEGERI SUMBER BUNGUR PAMEKASAN - Wardi, Moch Cholid (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2017)
This writing is trying to analyze the effort of strengthening and internalizing the studentsâ Islamic characteristics through their pocket book. Based on the research data, MTsN Sumber Bungur pamekasan did a concrete way to strengthen the studentsâ Islamic characteristics by integrating them in every aspect of the lesson. Besides, there is also an effort to internalize the maslahah concept in the application of studentsâ rule that can be seen from violation clarification and also the punishment which categorized into serious, medium, and small violation. The application of violation clarification and punishment category given is a concept of Maslahah and practical guidance. In the context of maslahah, serious, medium, small violation can be suited into dharurah, hajiyah and tahsiniyah.Â  The concept of strengthening the studentsâ Islamic characteristics through the studentsâ pocket book in MTsN Sumber Bungur Pamekasan has done by giving punishment in the form of giving point from 0- 100 by giving violation clarification to serious, medium and small violation. The internalization of Maslahah concept through the students pocket book in order to strengthen the studentsâ Islamic characteristics in MTsN Sumber Bungur Pamekasan is the application of Maslahah Dharuriyah, Maslahah Hajiyah and Maslahah Tahsiniyah which in practice it belongs to serious, medium, and small violation which oriented on the effort to bring goodness, peaceful, comfortable situation appropriate with the Sharia.